1998
DOI: 10.1159/000026500
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Blood Levels of Tumor Necrosis Factor-Alpha in Patients with Obsessive-Compulsive Disorder

Abstract: To investigate immune system function in obsessive-compulsive disorder (OCD) we measured plasma levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in 14 drug-free obsessive-compulsive patients and 14 matched healthy controls. No significant differences were observed between patients and controls in plasma levels of IL-1β and IL-6, whereas plasma levels of TNF-α were significantly lower (p = 0.001) in the former. Blood levels of prolactin did not differ between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 20 publications
3
27
3
2
Order By: Relevance
“…Results of the study demonstrate that OCD patients had significantly higher levels of IL 2,4, 6,10 and TNF-α compared to healthy controls. However few studies did not find increased levels of TNF, IL-1 or IL-6 (Maes et al, 1994;Brambilla et al, 1997;Weizman et al, 1996;Monteleone et al, 1998;Carpenter et al, 2002;Denys et al, 2004) possibly due to the confounding effects of comorbid mood disorder and medications as reported in metaanalysis (Gray and Bloch, 2012). Importantly, results of current study are in accord with an earlier study reporting increase in interleukin-6 and TNF-alpha levels in drug free patients with OCD (Konuk et al, 2007) and another recent study reporting absence of correlation between antidepressant medication dose and cytokines, chemokines except sTNFr2 (Fontenelle et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results of the study demonstrate that OCD patients had significantly higher levels of IL 2,4, 6,10 and TNF-α compared to healthy controls. However few studies did not find increased levels of TNF, IL-1 or IL-6 (Maes et al, 1994;Brambilla et al, 1997;Weizman et al, 1996;Monteleone et al, 1998;Carpenter et al, 2002;Denys et al, 2004) possibly due to the confounding effects of comorbid mood disorder and medications as reported in metaanalysis (Gray and Bloch, 2012). Importantly, results of current study are in accord with an earlier study reporting increase in interleukin-6 and TNF-alpha levels in drug free patients with OCD (Konuk et al, 2007) and another recent study reporting absence of correlation between antidepressant medication dose and cytokines, chemokines except sTNFr2 (Fontenelle et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Despite the strong association between OCD and neuroinflammation, only few studies have examined cytokine abnormalities in OCD. However, findings from these studies are inconsistent; while few studies reported altered levels of cytokines (Brambilla et al, 1997;Denys et al, 2004;Fluitman et al, 2010;Konuk et al, 2007;Monteleone et al, 1998) others reported absence of difference compared to controls (Maes et al, 1994;Weizman et al, 1996;Marazziti et al, 1999;Carpenter et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Decreased TNF-α plasma levels in patients with OCD have also been reported by Denys et al, Brambilla et al, and Monteleone et al [25][26][27] Additionally, one study found markedly increased TNF-α levels in patients with early-onset OCD accompanied by anxiety or depressive disorder. 22 As demonstrated by the meta-analysis results noted above, depression seems to play a role in the higher TNF-α levels.…”
Section: Discussionsupporting
confidence: 63%
“…A number of early reports on serum and cerebrospinal fluid cytokine levels in OCD yielded discrepant results (Brambilla et al 1997;Mittleman et al 1997;Monteleone et al 1998;Denys et al 2004). Leckman et al (2005) measured plasma levels of a broad array of cytokines in 46 pediatric TD patients and 31 healthy controls, reporting increased baseline levels of tumor necrosis factor-alpha (TNF-a) and interleukin-12 (IL-12).…”
Section: Serologic and Prospective Studiesmentioning
confidence: 99%